Current and future alternative therapies for beta-thalassemia major - de Dreuzy, Edouard (Biomed J, 2016)
Beta-thalassemia is a group of frequent genetic disorders resulting in the synthesis of little or no β-globin chains. Novel approaches are being developed to correct the resulting α/β-globin chain imbalance, in an effort to move beyond the palliative management of this disease and the complications of its treatment (e.g. life-long red blood cell transfusion, iron chelation, splenectomy), which impose high costs on healthcare systems. Three approaches are envisaged: fetal globin gene reactivation by pharmacological compounds injected into patients throughout their lives, allogeneic hematopoietic stem cell transplantation (HSCT), and gene therapy. HSCT is currently the only treatment shown to provide an effective, definitive cure for β-thalassemia. However, this procedure remains risky and histocompatible donors are identified for only a small fraction of patients. New pharmacological compounds are being tested, but none has yet made it into common clinical practice for the treatment of beta-thalassemia major. Gene therapy is in the experimental phase. It is emerging as a powerful approach without the immunological complications of HSCT, but with other possible drawbacks. Rapid progress is being made in this field, and long-term efficacy and safety studies are underway.